PEGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS MACROMEDIA AUTHORWERE 7.0 UNTUK MEMFASILITASI KEMAMPUAN PEMAHAMAN KONSEP DAN MINAT BELAJAR BAHASA INGGRIS - Hermawan Wahyu Setiadi, Juang Kurniawan (Universitas PGRI Yogyakarta, 2018)
This study aims to develop English-based learning media macromedia authorwere 7.0 to determine the quality and effectiveness of learning media developed.Population in this research is all of second graders of elementary school in Bibis academicyear 2017/2018, with sample as many as 56 students. Sampling in this study usingNonprobability Sampling technique Data understanding of learning concepts collectedusing tests and interest in learning English was collected through questionnaires. Thisresearch uses ADDIE development design. Data analysis technique used is descriptivestatistic which analyzed by using t test. The results of product quality assessmentrecapitulation from media experts and material experts indicate that the developed productincludes good criteria with mean of 81 so it is feasible in English learning. The resultsshowed that the attractiveness of students and teachers based on responses showed a meanof 86 with very good criteria. The results showed that the attractiveness based onobservation in the trial was limited and the extensive test showed that the average of 80indicated good criteria. The average posttest class score is 88.50 and the average posttestclass score is 80.58. In the study showed t count of 7,730 and t table equal to 2,021. So ttestof posttest shows that t count > t table and significance value obtained 0,00 <0,05which mean there is difference mean of posttest English value between experiment classand control class where the average value of posttest class the experiment is higher thanthe average value of the control class posttest. Based on the results of this study can beconcluded that learning using media-based learning authorwere 7.0 proved more effectiveto understanding the concept and interest in English learning fourth grade students BibisElementary School.Keywords: Learning Activity, Macromedia Authorwere Interactive Media 7.0, LearningInterest.